Vida vivida: experiencias de morbilidad materna extrema. Relatos de mujeres sobrevivientes y cuidadoras. Subregión del Urabá antioqueño, 2016 (2018)
ABSTRACT: To interpret the experience of women survivors and caregivers with regards to facing an event of extreme maternal morbidity in the subregion of Urabá, Antioquia 2016. Methodology: Autobiographical narrative research, which seeks to reconstruct the experience through a reflective process. A selection process was carried out for women survivors of extreme maternal morbidity and their caregivers, and in-depth conversational interviews were conducted for the construction of the narratives. The stories were transcribed textually and an interpretative process was made using an instrument that takes into account three mimetic moments based on Paul Ricoeur’s theory of the hermeneutic arc. Furthermore, ethical considerations relevant to this type of research were taken into account. Results: The story of surviving extreme maternal morbidity in Urabá gives meaning to the resignification of human care and the recognition of human capabilities. Conclusions: With the emergence of feelings of practical rationality, affiliation and emotions in the stories of survivors and caregivers, the experience of extreme maternal morbidity, understood as a narrative event, is shown in a richer and more humane way. The capabilities approach proposed by Nussbaum makes it possible to assess the quality of life, identify limitations of the social environment in order to unfold them, and reveal the absence of capabilities, inequality and ignorance of rights. This opens an area of study regarding life stories of extreme maternal morbidity from an ethical and political perspective of social justice in health.